2020
DOI: 10.1063/1.5129616
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature phonon studies and evidence of structure–spin correlations in MnV2O4

Abstract: We report here, temperature dependent Raman spectroscopic measurements on polycrystalline MnV2O4 over the temperature range of 10–300 K. The main aim of this study is to investigate the spin–phonon correlations across the magnetic and structural transition temperatures in this system. Temperature dependent magnetization measurements combined with the low temperature Raman study show the existence of structural changes in MnV2O4 across the two successive phase transitions. Anomalous changes in line shape parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Strain appears to be a key aspect of stripe domain formation in MVO and MMO. As reported in our previous publication 25 , coordinated appearance of the stripe domains in maps of surface magnetization required the presence of mechanical stress as the samples proceed through their respective magnetostructural transitions, not inconsistently with bulk data in the literature 23,35,42 . This is also borne out by the magnetization data presented in Fig.…”
Section: The Effect Of Strainsupporting
confidence: 64%
See 1 more Smart Citation
“…Strain appears to be a key aspect of stripe domain formation in MVO and MMO. As reported in our previous publication 25 , coordinated appearance of the stripe domains in maps of surface magnetization required the presence of mechanical stress as the samples proceed through their respective magnetostructural transitions, not inconsistently with bulk data in the literature 23,35,42 . This is also borne out by the magnetization data presented in Fig.…”
Section: The Effect Of Strainsupporting
confidence: 64%
“…The exact mechanism behind the observed magnetodielectric effects is unknown, but such phenomena can arise in non-polar insulators from a coupling between optical phonons and local spins 16 . At low temperature, MVO 32,41,42 develops orbital order on the vanadium sublattice, greatly enhancing the spin-lattice coupling in this material. One might expect that phonons coupling to the resulting antiferromagnetic modulation would produce a highly anisotropic dielectric tensor with respect to the c-axis; field-induced rearrangement of the c-axis domain structure would then yield large changes in the macroscopic capacitance far below the ordering transition.…”
Section: Comparison To Bulk Response Functionsmentioning
confidence: 99%
“…The unassigned mode (marked with an asterisk in Figure 1b) may originate from cation disorder or partial inversion, both of which are typical phenomena in spinel oxides [38,39]. The experimentally observed vibrational frequencies are compared in Table 1 with those of DFT calculations, and also with literature values for isostructural CoV 2 O 4 and MnV 2 O 4 [40,41]. It is found that DFT calculations overestimate the frequencies of the three low-frequency modes and underestimate the frequencies of the two high-frequency ones.…”
Section: Ambient Conditions Sample Characterization Of Starting Mater...mentioning
confidence: 96%